Problems in milpa agriculture - Skutch, Alexander F. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The following remarks are based chiefly upon my experience in El General, Costa Rica, where I have lived for most of the past fifteen years. For eight of these years I have farmed on a small scale. El General is the name given to the expanded basin at the head of the valley of the Rio Térraba, the major river in the Pacific drainage of southern Costa Rica. The lower parts of the basin lie at about 1500 feet above sea-level. Cultivation extends far up the surrounding mountain slopes, but most of the farm lands are sit uated between 2000 and 4000 feet.